Coupling effect of porosity and hydrate saturation on the permeability of methane hydrate-bearing sediments - Shen, Pengfei; Li, Gang; Li, Bo; Li, Xiaosen (Fuel, 2020)
The water effective permeability (k(w)) of the methane hydrate-bearing sediments is a key parameter in the investigation of natural gas exploitation, and it is closely related to hydrate saturation (S-H) and the initial porosity of sediments. In this work, the effect of S-H on the k(w) were systematically investigated in different initial porosities of fine quartz sands. The results show that the initial porosity of sediments has significant influence on the k(w) of the sediments with and without methane hydrates, and the hindrance of methane hydrates was more pronounced in the sediments with higher initial porosity. The stability and decomposition process of hydrates in this study could be clearly measured by the differential pressure of the sediments, and the stability of hydrates during the permeability measurement was more than 3 h, which was new record in permeability measurement. Finally, a new reduction empirical model on the basis of simple cubic model and oblique cubic model was integrated, and the effect of initial porosity of sediments on water relative permeability could be eliminated. This model could provide a more accurate prediction of the permeability of hydrate reservoirs with the porosity variation of the sediment.